2020
DOI: 10.26434/chemrxiv.13284416.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enantioselective Access to Dialkyl Amines and Alcohols via Ni-Catalyzed Reductive Hydroalkylations

Abstract: Chiral dialkyl amines and alcohols are ubiquitous in pharmaceuticals, pesticides, natural products and fine chemicals, yet difficult to access due to the challenge to differentiate between the spatially and electronically similar alkyl groups. Herein, we report a nickel-catalyzed enantioselective reductive hydroalkylation of enamides and enolates with alkyl halides to afford enantioenriched α-branched aliphatic amines and alcohols in good yields with excellent levels of enantioselectivity. The operationally si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…alkyl halides are challenging to prepare, as functionalized alkenes are readily accessible than their functionalized alkyl halide counterparts. 35,36 Most recently, Hu's group, Shu's group, and our group independently demonstrated that the carbon stereocenter could be controlled using achiral enamides [37][38][39] and alkenyl boronates, 40 namely hydroalkylation of enamides or alkenyl boronates to produce enantioenriched aliphatic amines or alkyl boronates. In this context, we envisioned that this new strategy might realize the direct catalytic asymmetric synthesis of enantioenriched dialkyl carbinols and their derived esters (Scheme 1d).…”
Section: Obocmentioning
confidence: 99%
“…alkyl halides are challenging to prepare, as functionalized alkenes are readily accessible than their functionalized alkyl halide counterparts. 35,36 Most recently, Hu's group, Shu's group, and our group independently demonstrated that the carbon stereocenter could be controlled using achiral enamides [37][38][39] and alkenyl boronates, 40 namely hydroalkylation of enamides or alkenyl boronates to produce enantioenriched aliphatic amines or alkyl boronates. In this context, we envisioned that this new strategy might realize the direct catalytic asymmetric synthesis of enantioenriched dialkyl carbinols and their derived esters (Scheme 1d).…”
Section: Obocmentioning
confidence: 99%
“…1c). Here, we report the Ni-H-catalyzed regio-and enantioselective hydroalkylation of acyl enamines and enol esters with alkyl iodides to forge a stereogenic carbon center next to nitrogen or oxygen originating from alkenes in high enantioselectivity, providing a unified protocol for rapid access to chiral secondary alkyl-substituted amine and alcohol derivatives which are difficult to access otherwise [50][51][52] .…”
mentioning
confidence: 99%
“…Herein, we reported the Ni-H catalyzed regio-and enantioselective reductive hydroalkylation of acyl enamines and enol esters with alkyl iodides to forge a stereogenic carbon center next to nitrogen or oxygen original from alkenes in high enantioselectivity, providing a uni ed protocol for rapid access to chiral dialkyl amine and alcohol derivatives which are di cult to access otherwise. [49][50][51] To test the feasibility of the reaction, we set out to identify the reaction parameters using acyl enamine 1a with 1-iodo-3-phenylpropane 2a as substrate in the presence of silane. (Table 1 and Tables S1-13).…”
mentioning
confidence: 99%